The Relationship between Religiosity and the Bystander Effect with Prosocial Behavior in College Students - Naja, Nihayatun; Ruddin, Fajar (Universitas Muhammadiyah Surakarta, 2025)
Purpose: In the academic environment, students are still found to have low prosocial behavior. College students are individuals in the emerging adulthood stage, the period between the ages of 18 and 29. Key characteristics of this period include identity exploration, the process of identifying and understanding oneself; instability in relationships, work, and housing; a focus on oneself; a feeling of being